(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
The origin of the relationship between landscape and atmosphere in the literary text must be sought first and foremost in the prototypical Stimmung that characterizes a given culture and from which, the specific interaction between man and the environment in a certain space, arises. In this sense, each literature will be a mirror of the specific contractive or expansive tendencies that characterize this interaction. Taking this into consideration, this article proposes a reading of the relationship between the Russian culture and the urban landscape, mentioning the possible identification of a real ‘Russian urban text’, in which the novel My by Y. Zamyatin can also be included as an example.